Gaseificação da biomassa fecal para produção de biocombustível : estudo da conversão termoquímica e avaliação exergoecológica - Dalvi, Elias Antonio (2015)
The present work is a study of human fecal biomass as a source of renewable alternative energy. The average Calorific Value and the Calorific Value depending on caloric diet allowed the determination of the energy potential of biomass worldwide, by continent and country. An analysis offeces of otheranimalswas also performedand comparedtothe humanfecesunder the caloricpoint of view,using the concept ofRejectedEnergyIndex(IER,in Portuguese) which is the energyrejectedper kilogram of body weight,and it was found that for humanis the smallest. The use of human feces in the batch reactor simulating a gasifier downdraft yielded results and preliminary findings for later use in a downdraft gasifier with 20 kW capacity, using 0%, 10% and 20% moisture content and particle diameters of 15, 30 and 50 mm. A feasibility study was also carried out on theuse of gasification technology as an alternative system for the treatment of feces, taking the concept of exergy as reference by means of two parameters: environmental exergetic efficiency, defined as the exergy ratio of the useful effect of the process to the total exergy consumed by human and natural resources, including all the exergy inputs.The renewabillity calculation was done using the Renewabillity Exergy Index defined as the exergy ratio of the products to the sum of the non-renewable exergyanddestroyedexergy.Finally,atable was assembled which shows theenvironmentalexergyefficiencyparameters andthe exergeticindexrenewabilitydeterminedin this work as compared bythe sameparameters determinedbyBEJARANO(2009) forthree of sewagetreatmenttechnologies: SewageBarueriTreatment Plant(Brazil ), RAFA-Facultative Pond(Brazil) andCañavelarejoSewageTreatment Plant(Colombia); Theresults, althoughillustrative, indicate thatgasificationmay becomeanadvantageousstep to be used inasewage treatment system.